Letter from Campbell Morfit to James Curtis Booth, February 28, 1860 - Morfit, Campbell (1860)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), requests that Booth nominate a friend for an honorary degree from the New York Medical College.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; New York Medical College